النظرة الحديثة لتشخيص وعلاج التهاب المثانة الحاد البدئي عند النساء - حرفوش, أيمن (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 84 مريضة مصابة بالتهاب مثانة حاد بدئي في مشفى الأسد الجامعي باللاذقية بين عامي 2004 - 2006. قسم هذا العدد إلى مجموعتين متساويتين. عولجت المجموعة الأولى بالنورفلوكساسين لمدة خمسة أيام. والمجموعة الثانية أيضاً بالنورفلوكساسين ولكن لمدة عشرة أيام. وأجريت مقارنة علاج المجموعتين. أكثر الجراثيم تسبياً بالتهاب المثانة الحاد البدئي كانت E.coli حيث وجدت عند 73 مريضة (86.9%). عدد الحالات المقاومة للنورفلوكساسين بلغت 8 حالات (9.52%) من مجموع الحالات. تم الحصول على نتيجة ايجابية عند 75مريضة (89.28%) من مجموع الحالات المعالجة. لم نجد فارقاً كبيراًً بين معالجة مريضات المجموعة الأولى لمدة خمسة أيام ومعالجة مريضات المجموعة الثانية لمدة عشرة أيام. ولمعالجة التهاب المثانة الحاد البدئي تكفي خمسة أيام لزوال الأعراض السريرية والتغيرات في فحص البول والراسب. The study covered 84 women of primary acute cystitis in Al-Assad University Hospital in Lattakia in 2004-2006. This number was divided into two equal groups. The first group was treated with Norfloxacine 400 mg for five days. The second group was also treated with Norfloxacine 400 mg but for 10 days. There had been a comparison between the two treatments. Most of germs which caused the primary acute cystitis were E. coli. They had been found in 73 women (86.9%). There had been 8 cases (9.52% of the total cases) which resisted Norfloxacine 400 mg. A positive result was obtained in 75 women (89.28% of the total treated cases). There was a big difference between the treatment of the first group for 5 days and the treatment of the second group for 10 days. Consequently, 5 days are enough for to get rid of the clinic symptoms and the changes in examining urine and deposit.